Kebijakan Penanggulangan Narkotika oleh Badan Narkotika Nasional Ditinjau dari Undang-Undang Narkotika - Khoirullah, Muhamad Satria; Hutabarat, Rugun Romaida (Legal Standing : Jurnal Ilmu Hukum, 2025)
This research stems from the obligation of a rule-of-law state to protect its citizens from the threat of narcotics abuse, which is increasingly widespread and endangering the nation’s survival. The purpose of this study is to explain the obstacles faced by the National Narcotics Agency (BNN) of Tangerang City in implementing law enforcement policies against narcotics crimes in its jurisdiction. This research employs an empirical legal method using a juridical-empirical approach, combining analysis of legal regulations with field data obtained through interviews, documentation, and literature studies. The findings show that although BNN Tangerang City has carried out various prevention, eradication, and rehabilitation policies through cross-sectoral cooperation with local governments, the police, and the community, implementation still faces serious challenges, such as shortages of human resources, limited operational facilities, weak inter-agency coordination, and gaps in technical understanding related to proving narcotics cases. In addition, the participation of Regional Government Organizations (OPD) is considered uneven, and private sector involvement remains minimal. This research recommends the need for increased budget allocation, recruitment and training of human resources, strengthening of forensic laboratories, optimization of technology, and regulatory improvements to create a more effective and sustainable narcotics control system in Tangerang City.